Sebuah Rancang Bangun M-Learning Interaktif berbasis Client-Server pada Mata Pelajaran Komputer dan Jaringan Dasar di SMK Negeri 1 Painan - Chairana, Syalma Audhia; Hadi, Ahmaddul (Jurnal Teknik Komputer dan Informatika, 2024)
This research aims to design and develop a client-server based interactive M-Learning system for Basic Computer and Network subjects at SMK Negeri 1 Painan. M-Learning is a modern learning approach that utilizes mobile technology to facilitate the learning process where students can access learning materials anytime and anywhere via their mobile devices. In this media the author integrates client-server technology to create a more interactive M-Learning platform, where teachers can CRUD (Create, Read, Update, Delete) learning content managed on a web server. This system allows teachers to upload lesson materials, assignments and other supporting resources to the server. Students can access these materials through a special application on their mobile devices. With the implementation of M-Learning, it is hoped that learning will become more dynamic and easily accessible. Teachers can be more effective in providing learning material, while students have the flexibility to learn according to their own rhythm. This m-learning media was tested using the Black Box method to ensure whether the system created was according to design or not. And the results, based on the test table, can be concluded that the entire interactive m-learning functionality has been fulfilled and declared successful in accordance with its respective functions and objectives.